Structural changes and molecular mechanisms of bone remodelling in two different regions of subchondral bone during early osteoarthritis - Akman, Akma Azmiera; Abdul Ghani, Radiah; Zamli, Zaitunnatakhin (2018)
Osteoarthritis (OA) is a degenerative joint diseases that progressed as a function of age. Previous studies have shown that the structural changes of osteoarthritic subchondral bone are associated with rapid bone remodelling, and differed between its two regions; subchondral bone plate (Sbp) and trabecular bone (Tb). Despite of extensive studies in human and animal models of OA, the molecular mechanisms that underlying the differences between these two regions have yet to be determined. Hence, the present study aims to determine the structural changes and molecular mechanisms of Sbp and Tb during development of OA in Dunkin Hartley guinea pigs. To achieve these aims, the Sbp and Tb thickness of the tibia was determined by using a micro-computed tomography (micro-CT) at 10, 20 and 30 weeks of age. The level of bone resorption (i.e. Receptor activator of NF-κB ligand) and formation (i.e. osteoprotegerin) markers was quantified by using immunohistochemistry technique. The severity of the disease was microscopically scored by histopathology technique. The results showed that Sbp and Tb thickness were greater in the medial than the lateral side of tibial plateau, and increased significantly with ageing (p ≤ 0.01). In addition, across the time points, the OPG/RANKL ratio of medial Sbp was initially increased, before being decreased at the final time point. In contrast, the OPG/RANKL ratio of medial Tb was initially constant but then decreased at 30 weeks of age. The data also showed that the AC degeneration was more pronounced in the medial than the lateral side, and worsen with ageing. Interestingly, a strong correlation was observed between the Sbp thickness and OPG/RANKL ratio with microscopic OA scores (r = 0.5, p ≤ 0.05), suggesting that the Sbp plays an important role in the pathogenesis of OA.